Prototipe Turbin Angin Savonius Pada Kecepatan Angin Skala Kecil Untuk Pengisian Baterai - Latif, Melda; Farizi, AL; Muharam, Mumuh; Laksono, Heru Dibyo; Yunus, Syukri; Rajab, Abdul; Fitrilina, Fitrilina (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2022)
The Vertical Axis Wind Turbines are very suitable for use in areas with very low wind speeds. This research makes a prototype of the Savonius wind turbine to produce electrical energy as an energy source to 2 x 3.7 Volt dry battery. The Savonius turbine has four blades made of PVC. The controller circuit consists of a Boost Converter circuit and an astable multivibrator. At a speed of 2.7 m/s, the wind turbine starts to rotate and produces a no-load voltage of 0.3 V. At a speed of 3.7 m/s a voltage of 2 V is generated and can charge the battery. By using an LED (Light Emitting Diode) in the controller circuit, the charged battery can be a source of voltage in the controller circuit and the LED indicator light can be lit.